Local Perception Of The Carbon Emission Reduction Program In Oil Palm Plantations - Faisal, Andi Fahri (Moccasin Journal De Public Perspective, 2024)
This study aims to examine local community perceptions of carbon emission reduction programs in oil palm plantation areas, focusing on awareness, perceived benefits, and participation. A qualitative case study approach was employed, involving semi-structured interviews with 25 participants, including smallholder farmers, plantation workers, community leaders, and local government representatives. Data were analyzed using thematic analysis to identify key patterns in community responses. The findings reveal varying levels of awareness, with some participants demonstrating a clear understanding of environmental objectives while others showed limited comprehension. Economic considerations were found to dominate perceptions, with most participants prioritizing tangible benefits such as income and employment. In addition, limited participation in decision-making processes contributed to skepticism and reduced trust in the program. The study concludes that the effectiveness of carbon emission reduction programs depends not only on technical design but also on community engagement, equitable benefit distribution, and context-sensitive communication strategies.